Metaphor in a Short Story of Sepasang Wajah di Bilik Suara by Indra Tranggono: A Stylistic Study - Inayah Isnaini Faizah; Linda Eka Pradita (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
Short story is a literary work in the form of fictional prose that tells about experienced by the main character. This study aims to describe the form and meaning of metaphors contained in the short story Sepasang Wajah dalam Bilik Suara by Indra Tranggono. This research method is descriptive qualitative. This research uses the reading-note technique. The data source in this research is the short story A Pair of Faces in the Sound Room. The results of this study found forms of metaphor which include 7 anthropomorphic, 4 animalistic, 3 abstraction, and 7 synesthetic, so that it has aesthetic value and the way of description is more creative and expressive. In addition, there are also stylistic elements such as lexical meaning, grammatical meaning, cohesion, structural investigation, simile and imagery in short stories.